A gold-catalyzed facile intramolecular rearrangement and cyclization sequence for synthesis of 2, 5-dihydrofurans. Issue 24 (3rd June 2019) - Sunil, Komalla; Thummala, Yadagiri; Dalovai, Purnachandar; Balasubramanian, Sridhar; Karunakar, Galla V.
Abstract : An efficient gold-catalyzed intramolecular rearrangement and cyclization protocol was developed for synthesis of 2, 5-dihydrofuran derivatives via formation of a new C–C and C–O bond with a quaternary centre. Abstract : An efficient gold-catalyzed intramolecular rearrangement and cyclization protocol was developed for synthesis of 2, 5-dihydrofuran derivatives from O -propargyl β-enaminones. In this organic transformation new C–C and C–O bonds are formed under mild reaction conditions; this includes the formation of a quaternary centre.